Modelling organisational citizenship behaviour for secondary school teachers: the associating factors of principal support, organisational justice, meaningful work and professional commitment / Nurharani Selamat - Selamat, Nurharani (2017)
As a country that aims to achieve high-income and developed nation status by 2020, Malaysia is in dire needs to improve the quality of education. Teachers are seen as key players in fulfilling the demands of high quality education especially teachers who are willing to demonstrate extra-role behaviour which is termed as organisational citizenship behaviour (OCB). Despite the cruciality of OCB in determining quality of education, scholars could not find a consensus on the best dimensions to constitute teachers‟ OCB. Furthermore, research on teacher‟s OCB remains scarce due to the lack of awareness regarding the contributions of OCB to enhance school effectiveness as compared to business organisations. Thus, this study has attempted to test and validate the alternative model for teachers‟ OCB, known as The Teacher‟s Triangular OCB Model. Moreover, drawing on social exchange theory and psychological ownership theory, and supported by organisational citizenship behaviour theory, organisational justice theory, social support theory, professional commitment theory, and workplace spirituality theory, this study aims to examine the effect of principal support, organisational justice, meaningful work, and professional commitment on OCB among secondary school teachers. A quantitative approach and cross-sectional survey strategy was employed as the research method of this study. As for sampling technique, a proportional stratified sampling technique was applied to collect data from 395 regular secondary school teachers in Selangor. The data collected was analysed using descriptive analysis and structural equation modelling to test the 11 hypotheses of this study. The result suggested that the alternative model for teachers‟ OCB is valid, reliable, and consists of three distinguishable dimensions, namely, affiliative oriented OCB, change oriented OCB, and innovative oriented OCB. The results showed that principal support, meaningful work, and professional commitment were significant predictors of OCB. In addition, professional commitment was found to mediate the relationships between principal support and meaningful work with OCB. However, the hypothesised relationships between organisational justice with professional commitment and OCB were not supported. Thus, based on the findings, theoretical and practical implications were discussed and several recommendations for practice and future research were proposed. In conclusion, this study has provided empirical evidence on the alternative model of OCB in a school context, specifically in the Malaysian secondary school. This study also has provided empirical evidence that social exchange predictors and psychological ownership predictors could be integrated into one model to explain significant factors that could influence teachers to demonstrate OCB.